Analisis Tingkat Kepuasan Mahasiswa Terhadap Pembelajaran Daring Di Era Pandemi - Nadya Ulfa Salfirah; Firanti Nuur; Elza Rachman Panca Priyanda (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Terbuka, 2022)
Online learning is the right Alternative for learning during the Covid-19 pandemic.The success rate of an online learning service is seen from the level of student satisfaction as the recipient of the service. However, based on the results of these researchers showed a lack of student satisfaction with this online learning.The purpose of this study was to see the level of satisfaction of STIKes Har-Kausyar students towards the online learning process in the era of the Covid-19 pandemic by distributing questionnaires to all STIKes Har-Kausyar students from semesters 1-7. There are five dimensions used in this study, namely: tangible evidence (tangible), reliability (reliability), responsiveness (responsiveness), assurance (assurance), and empathy (empathy). The conclusions obtained show that STIKes Har-Kausyar students are less satisfied with online learning in the mass of the Covid-19 pandemic.